Associations of TyG index with coronary heart disease risk and coronary artery sclerosis severity in OSA - Xuan Qiu; Gulimire Aimaiti; Yulan Chen; Yu Li; Xiaojing Sun (Diabetology & Metabolic Syndrome)
Abstract Background Insulin resistance (IR) is involved in the pathogenesis and progression of obstructive sleep apnea (OSA) and coronary heart disease (CHD). The triglyceride glucose(TyG) index, an alternative indicator of IR with high reliability, is linked to CHD development and severity. However, the association of TyG index with CHD in OSA cases remains undefined. This study explores the association of TyG index with CHD risk and coronary artery sclerosis severity in the OSA population. Methods OSA cases with suspected CHD, enrolled at the Department of Hypertension, The First Affiliated Hospital of Xinjiang Medical University between February 2020 and June 2024, were assigned to the OSA and OSA + CHD groups, followed by TyG index assessment. The t-test, Mann-Whitney U-test and one-way analysis of variance were utilized to compare continuous data, while comparisons of categorical data utilized the chi-square test or Fisher’s exact test. Logistic regression analysis was conducted to determine factors independently predicting OSA with CHD and Gensini scores. Restrictive cubic spline (RCS) was used to assess potential non-linear associations of TyG index with CHD risk and Gensini score in OSA patients. Results Totally 1059 OSA patients were included, with 514 diagnosed with CHD (48.54%). Multivariable logistic regression analysis upon adjustment for age, gender, hypertension, diabetes, and smoking history revealed TyG index as a risk factor for CHD in OSA cases. CHD risk in the high-TyG index group was 1.977 fold higher versus the low-TyG index group (OR = 1.977, 95% CI 1.424-2.800, P < 0.001). In addition, TyG index had a linear relationship with CHD (P for nonlinearity = 0.0709). In moderate to severe OSA cases, the high-TyG index group had a significantly higher CHD risk (OR = 2.430, 95% CI 1.601–3.690, P < 0.001). Gensini score and TyG index (P for non-linearity = 0.0033) had a non-linear relationship, while high TyG index was a risk factor for high Gensini score. Conclusion TyG index is a risk factor for CHD in OSA cases and reflects the severity of coronary atherosclerosis. TyG, a surrogate indicator for IR evaluation, may help predict CHD in OSA cases, especially in moderate to severe OSA.